Reproducibility of Peripapillary Retinal Nerve Fiber Layer and Macular Retinal Thickness Measurements Using Optical Coherence Tomography - Sheng-Yao Hsu; I-Chen Tung; Min-Muh Sheu; Rong-Kung Tsai (Kaohsiung Journal of Medical Sciences, 2006)
We investigated the interoperator reproducibility of peripapillary retinal nerve fiber layer (RNFL) and macular retinal thickness measurements using optical coherence tomography (OCT) in healthy Taiwanese eyes. In this study, OCT-3 was used by three trained and experienced operators to measure peripapillary RNFL and macular retinal thickness in a randomly chosen single eye from each normal subject. Mean thickness levels and the differences in thickness measurements among the three operators were calculated and compared. The eyes of 39 subjects (24 females and 15 males) were enrolled. The mean age of the subjects was 30.4 ± 16.1 years (range, 11-46 years). The mean pupil diameter after pupillary dilation was 7.4 ± 0.6 mm (range, 6-9 mm). Comparing peripapillary RNFL and macular retinal thickness measurements after pupillary dilation, there were no significant differences in: superior, inferior, temporal, and nasal peripapillary areas; 6 mm total macular volume and foveal thickness; and 1, 3 and 6 mm perifoveal areas among the three operators. In this study, OCT thickness measurements showed good interoperator reproducibility among three trained and experienced operators.